Population genomics of the white-beaked dolphin (Lagenorhynchus albirostris): implications for conservation amid climate-driven range shifts - Gose, Marc-Alexander; Humble, Emily; Brownlow, Andrew; Wall, Dave; Rogan, Emer; Sigurðsson, Guðjón Már; Kiszka, Jeremy J.; Thøstesen, Charlotte Bie; IJsseldijk, Lonneke L.; ten Doeschate, Mariel; Davison, Nicholas J.; Øien, Nils; et al. (Heredity, 2024)
Climate change is rapidly affecting species distributions across the globe, particularly in the North Atlantic. For highly mobile and elusive cetaceans, the genetic data needed to understand population dynamics are often scarce. Cold-water obligate species such as the white-beaked dolphin (Lagenorhynchus albirostris) face pressures from habitat shifts due to rising sea surface temperatures in addition to other direct anthropogenic threats. Unravelling the genetic connectivity between white-beaked dolphins across their range is needed to understand the extent to which climate change and anthropogenic pressures may impact species-wide genetic diversity and identify ways to protect remaining habitat. We address this by performing a population genomic assessment of white-beaked dolphins using samples from much of their contemporary range. We show that the species displays significant population structure across the North Atlantic at multiple scales. Analysis of contemporary migration rates suggests a remarkably high connectivity between populations in the western North Atlantic, Iceland and the Barents Sea, while two regional populations in the North Sea and adjacent UK and Irish waters are highly differentiated from all other clades. Our results have important implications for the conservation of white-beaked dolphins by providing guidance for the delineation of more appropriate management units and highlighting the risk that local extirpation may have on species-wide genetic diversity. In a broader context, this study highlights the importance of understanding genetic structure of all species threatened with climate change-driven range shifts to assess the risk of loss of species-wide genetic diversity.